Employee Performance at the Office of Population and Civil Registration in North Morowali Regency - Jumiani, Jumiani; Hattab, Syahruddin; Faisal, Muhammad (PINISI Discretion Review, 2018)
This study aims to find out how the Performance of Employees in the Office of Population and Civil Registry of North Morowali Regency. This type of research used is descriptive and the basic research used is qualitative research methods. The informants in this study were determined positively by the number of informants as many as 7 people, data collection techniques through observation, interviews and documentation. In this study using Suyadi Prwirasentono's theory, where there are 4 (four) indicators that there are employee performance at the Office of Population and Civil Registration of North Morowali Regency in terms of effectiveness, authority and responsibility, discipline, initiative. Based on the results of existing research that the performance of employees at the Office of Population and Civil Registry of North Morowali Regency is considered quite good.